Post-traumatic fibro-osseous lesion of the ribs: a relatively under-recognised entity. Issue 6 (7th February 2006) - Aubert, S; Kerdraon, O; Conti, M; Buob, D; Petit, S; Leroy, X
Abstract : Aim: To report the description of a rare benign osseous lesion affecting the ribs entitled post-traumatic fibro-osseous lesion (PTFOL). Methods: Seven cases of PTFOLs were retrieved from the archives of the University Hospital of Lille. Histological slides were reviewed and lesions were classified according to the histological patterns described by McDermott et al . Clinical and follow-up data were obtained from the patients' charts. Results: PTFOLs occurred principally in men (mean age 31.8 years) with a known or suspected previous chest injury for four of them. No previous cancer was noted. Radiologically, PTFOLs readily presented as an isolated expansive lucency with a sclerotic rim located on the last five ribs. A constant increased uptake of radionucleotide was noted on bone scan. Microscopically, two fibro-osseous, four xanthomatous and one mixed pattern were individualised. Lesions were characterised by a network of anastomosing bone trabeculae without osteoblast lining within a fibrous stroma. A zonal maturation from woven to peripheral lamellar bone was characterised. Central sheets of lipid-laden histiocytes were conspicuous in the xanthomatous type. For each patient, clinical follow-up was excellent, without any recurrence. Conclusions: This is the second largest series of PTFOLs, which is considered to be a dysplastic healing process after trauma. It may be symptomatic or shown by imaging studies realised for unrelated reason. PTFOL is regularly misdiagnosed with other more common lesions of the ribs, such as fibro-osseous dysplasia, osteoma osteoid and benign fibrous histiocytoma. Its recognition is of importance because no follow-up is needed after resection.